Intravaginal electrical stimulation for the treatment of pelvic floor dysfunction: a systematic review and meta-analysis - Chen, Rongrong; Wang, Rui; Yu, Yanmei; Zhao, Kun; Li, Juebao (Frontiers in Neurology, 2024)
Background: Intravaginal electrical stimulation (IVES) has been explored as a potential treatment for pelvic floor disorders (PFDs), although its efficacy remains a subject of debate. We aim to conducted a comprehensive meta-analysis of relevant trials.Methods: This meta-analysis was performed under the PRISMA 2020 guideline. We meticulously searched for randomized controlled trial (RCT) studies in various databases, including PubMed, Cochrane Library, EMBASE, and ClinicalTrials.gov, spanning from inception to March 6, 2023. All studies included one treatment group of intravaginal electrical stimulation and the diseases spectrum of the studies involved different kinds of PFDs, including urinary incontinence, overactive bladder, etc. Risk of bias charts were used to assess the risk of bias in the studies and forest plots were used the demonstrate the overall effects.Results: Our analysis encompassed a total of 13 RCT studies. In most of the assessed PFD cure outcomes, the results demonstrated positive effects of IVES therapy, as indicated by the following findings: daily voiding frequency (MD= -1.57, 95% CI = -3.08 to -0.06, I 2 = 68%,), nocturia (MD= -1.07, 95% CI = -2.01 to -0.13, I 2 = 71%), Pad test, and Urinary incontinence. Nevertheless, the data concerning the impact of IVES therapy on the quality of life of individuals with PFDs did not confirm these positive results.Discussion: In light of the insufficiency in both the quality and quantity of the included studies, it is premature to draw a definitive conclusion regarding the efficacy of IVES therapy for treating PFDs. Nonetheless, our study does provide several pieces of evidence in support of the potential therapeutic effects of electrical stimulation therapy in this context. We recommend that further research in this area be conducted to provide more conclusive insights into the efficacy of IVES therapy for PFDs.Others: There was no funding for this meta-analysis. This study was registered at prospero.com and the registration ID was CRD42023442171.